Hierarchizing the importance of the attributes of an online shared freight transportation service platform with the use of Multi-Actor Multi-Criteria Analysis (MAMCA). Issue 1 (November 2021) - Nalmpantis, Dimitrios; Genitsaris, Evangelos; Amprasi, Vasiliki; Akac, Attila; Anagnostopoulou, Afroditi
Abstract: The purpose of this paper is to hierarchize the importance of the attributes of an online shared freight transportation service platform with the use of Multi-Actor Multi-Criteria Analysis (MAMCA). A MAMCA was performed amongst the partners of the INTERREG Balkan-Med SCOPE project in order to hierarchize the attributes of such a platform which is under development in the frame of the project. The results show that all the actors agree that the most important criterion is the Service, i.e., the services that the platform will provide. The research institute and the chambers actors agree that the second most important criterion is Access, i.e., the interface of the platform, while the university actor thinks that Range is the second most important criterion, i.e., the service area of the platform. Probably, the actors who are closer to the market understand better the needs, requirements, and preferences of the users than academia, and that once you set up the platform for a specific Range, it can be easily expanded to cover more areas in the future. Nevertheless, it has to be underlined that these results have been derived by a very small sample, i.e., the partners of the SCOPE project and probably a broader MAMCA, including more stakeholders, should be performed in order to validate them.